Partisipasi Perempuan dalam Penyelenggaraan Pemilihan Umum di NTB Tahun 2019-2024 - Humaya, Siti; Jailani, Muhammad Aprian (JURNAL ILMIAH ILMU ADMINISTRASI, 2025)
This study analyzes women's participation in the conduct of General Elections (Pemilu) in the Province of West Nusa Tenggara (NTB) from 2019 to 2024. Women's participation is a crucial indicator of inclusive and representative democracy. The study aims to understand the efforts to increase women's participation in elections and the factors influencing their involvement. The method used is a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation at the NTB Election Commission (KPU NTB). The results show that despite efforts to increase participation, women still face various obstacles such as gender stereotypes and limited access to political resources. However, approaching the 2024 Election, there has been a significant increase in women's involvement, both as voters, legislative candidates, and election organizers. Affirmative policies and training programs organized by the Election Supervisory Body (Bawaslu) and the Election Commission (KPU) have contributed to this improvement. This study concludes that systematic efforts to overcome barriers to women's political participation can lead to significant improvements in their representation and involvement in the democratic process.